2011
DOI: 10.1890/es10-00152.1
|View full text |Cite
|
Sign up to set email alerts
|

The role of herbivores in Great Plains conservation: comparative ecology of bison and cattle

Abstract: Abstract. The Great Plains of North America evolved with significant influence from bison (Bison bison), but is presently dominated by cattle (Bos taurus). While there are a variety of opinions concerning differences between these two species, there is a lack of scientific comparisons, including those that incorporate important ecological variation. We developed a framework to study and compare the grazing behavior and effects of bison and cattle within grassland ecosystems. Environmental (e.g., resource distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
95
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 62 publications
(61 reference statements)
4
95
1
1
Order By: Relevance
“…For an animal with a mean weight of 250 kg, cattle require on average 30 L per day per individual, but this amount varied over time (Duesterhaus et al 2008). In a study of the comparative ecology of cattle and bison in tallgrass prairie in Oklahoma, USA, Allred et al (2011) showed cattle foraging close to permanent water sources, while bison spent more time at greater distances from permanent water sources. These authors concluded that ephemeral water sources may constitute an important fraction of the total drinking water consumed by bison (Allred et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For an animal with a mean weight of 250 kg, cattle require on average 30 L per day per individual, but this amount varied over time (Duesterhaus et al 2008). In a study of the comparative ecology of cattle and bison in tallgrass prairie in Oklahoma, USA, Allred et al (2011) showed cattle foraging close to permanent water sources, while bison spent more time at greater distances from permanent water sources. These authors concluded that ephemeral water sources may constitute an important fraction of the total drinking water consumed by bison (Allred et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of the comparative ecology of cattle and bison in tallgrass prairie in Oklahoma, USA, Allred et al (2011) showed cattle foraging close to permanent water sources, while bison spent more time at greater distances from permanent water sources. These authors concluded that ephemeral water sources may constitute an important fraction of the total drinking water consumed by bison (Allred et al 2011). Our results support Allred et al (2011) and highlight the significance of bison wallows as rainfall catchments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations